KV Channel-Interacting Proteins in the Neurological and Cardiovascular Systems: An Updated Review - Wu, Le-Yi; Song, Yu-Juan; Zhang, Cheng-Lin; Liu, Jie (Cells (Basel, Switzerland), 2023)
KV channel-interacting proteins (KChIP1-4) belong to a family of Ca2+-binding EF-hand proteins that are able to bind to the N-terminus of the KV4 channel α-subunits. KChIPs are predominantly expressed in the brain and heart, where they contribute to the maintenance of the excitability of neurons and cardiomyocytes by modulating the fast inactivating-KV4 currents. As the auxiliary subunit, KChIPs are critically involved in regulating the surface protein expression and gating properties of KV4 channels. Mechanistically, KChIP1, KChIP2, and KChIP3 promote the translocation of KV4 channels to the cell membrane, accelerate voltage-dependent activation, and slow the recovery rate of inactivation, which increases KV4 currents. By contrast, KChIP4 suppresses KV4 trafficking and eliminates the fast inactivation of KV4 currents. In the heart, IKs, ICa,L, and INa can also be regulated by KChIPs. ICa,L and INa are positively regulated by KChIP2, whereas IKs is negatively regulated by KChIP2. Interestingly, KChIP3 is also known as downstream regulatory element antagonist modulator (DREAM) because it can bind directly to the downstream regulatory element (DRE) on the promoters of target genes that are implicated in the regulation of pain, memory, endocrine, immune, and inflammatory reactions. In addition, all the KChIPs can act as transcription factors to repress the expression of genes involved in circadian regulation. Altered expression of KChIPs has been implicated in the pathogenesis of several neurological and cardiovascular diseases. For example, KChIP2 is decreased in failing hearts, while loss of KChIP2 leads to increased susceptibility to arrhythmias. KChIP3 is increased in Alzheimer’s disease and amyotrophic lateral sclerosis, but decreased in epilepsy and Huntington’s disease. In the present review, we summarize the progress of recent studies regarding the structural properties, physiological functions, and pathological roles of KChIPs in both health and disease. We also summarize the small-molecule compounds that regulate the function of KChIPs. This review will provide an overview and update of the regulatory mechanism of the KChIP family and the progress of targeted drug research as a reference for researchers in related fields.